2012
DOI: 10.1371/journal.pone.0032572
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Traction Stresses Increase with Increasing Metastatic Potential

Abstract: Cancer cells exist in a mechanically and chemically heterogeneous microenvironment which undergoes dynamic changes throughout neoplastic progression. During metastasis, cells from a primary tumor acquire characteristics that enable them to escape from the primary tumor and migrate through the heterogeneous stromal environment to establish secondary tumors. Despite being linked to poor prognosis, there are no direct clinical tests available to diagnose the likelihood of metastasis. Moreover, the physical mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
358
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 364 publications
(392 citation statements)
references
References 54 publications
(109 reference statements)
33
358
1
Order By: Relevance
“…We found that, when cultured on soft matrices, OCCs exerted more force (Fig. 1Eb), a characteristic that is often indicative of increased metastatic phenotype (Kraning-Rush et al, 2012). Previous work has demonstrated that during invasion into the submesothelial environment, OCCs use myosin-dependent traction force to escape the mesothelial cell layer (Iwanicki et al, 2011).…”
Section: Resultsmentioning
confidence: 64%
“…We found that, when cultured on soft matrices, OCCs exerted more force (Fig. 1Eb), a characteristic that is often indicative of increased metastatic phenotype (Kraning-Rush et al, 2012). Previous work has demonstrated that during invasion into the submesothelial environment, OCCs use myosin-dependent traction force to escape the mesothelial cell layer (Iwanicki et al, 2011).…”
Section: Resultsmentioning
confidence: 64%
“…Myosin II binds to actin and regulates F-actin assembly and disassembly dynamics (Murrell et al, 2015), and also regulates intracellular tension (or pre-stress) and cell contractility, which can contribute to cell stiffness Murrell et al, 2015). Indeed, cancer cells that exhibit greater traction stresses show increased invasive behavior in vitro (Kraning-Rush et al, 2012;Volakis et al, 2014) and in vivo (Paszek et al, 2005;Volakis et al, 2014). Our results suggest that βAR signaling could enhance the contractility of cancer cells.…”
Section: How Is Cell Stiffness Associated With Increased Invasion?mentioning
confidence: 64%
“…p130Cas is therefore likely to maintain its mechanosensing capability in cancer cells and tissues while remaining in the wild-type form. This notion is supported by the findings that show that traction force generation, which is the primary consequence of mechanosensing, 84 positively correlates with the cells' metastatic potential, 106 where p130Cas also plays a role. 3 Taken together, p130Cas may facilitate downstream signaling in cancer cells when provided with enhanced mechanical cues such as matrix stiffening or increased cellgenerated traction forces (Fig.…”
Section: Mechanical Regulation Of Src and P130cas Is Distinguished Bementioning
confidence: 69%